How the COVID-19 Lockdown Affected Gender Inequality in Paid and Unpaid Work in Spain - Lídia Farré; Yarine Fawaz; Libertad Gonzalez; Jennifer Graves (Institute of Labor Economics (IZA), 2020)
The covid-19 pandemic led many countries to close schools and declare lockdowns during the Spring of 2020, with important impacts on the labor market. We document the effects of the covid-19 lockdown in Spain, which was hit early and hard by the pandemic and suffered one of the strictest lockdowns in Europe. We collected rich household survey data in early May of 2020. We document large employment losses during the lockdown, especially in "quarantined" sectors and non-essential sectors that do not allow for remote work. Employment losses were mostly temporary, and hit lower-educated workers particularly hard. Women were slightly more likely to lose their job than men, and those who remained employed were more likely to work from home. The lockdown led to a large increase in childcare and housework, given the closing of schools and the inability to outsource. We find that men increased their participation in housework and childcare slightly, but most of the burden fell on women, who were already doing most of the housework before the lockdown. Overall, we find that the covid-19 crisis appears to have increased gender inequalities in both paid and unpaid work in the short-term.
Keywords: D13; J13; J16; 330; COVID-19; gender roles; labor market; household work; childcare